EFL STUDENT TEACHERS’ PERCEIVED KNOWLEDGE ON INTEGRATING ICT - Sarlita D. Matra; Salsabila Fitriana (University of Kuningan, 2022)
The integration of ICT in education forces teachers to be competent in using ICT instantly. Teachers are required to have qualified in ICT competencies. Especially in this pandemic era, teachers must have competencies in utilizing technology resource and skill to provide learning effectively both in real and virtual classroom. The purposes of this research are: 1) To find out whether EFL student teachers have perceived knowledge on integrating ICT after they study ICT in ELT course or not. 2) To explore how EFL student teachers’ perceived knowledge on integrating ICT after they study ICT in ELT course. The participants of this research were thirty-seven (37) student teachers of 5th semester English Education Department 2021/2022 UNIKAL. The data was collected by giving online questionnaire to the participants. The questionnaire measured the six variables of interests: student teachers’ knowledge on basic ICT tools and application, student teachers’ knowledge on theories, skills, strategies of ICT tools and application, student teachers’ knowledge on ICT online application, student teachers’ knowledge on ethics of using digital information, student teachers’ knowledge on class management skills and student teachers’ knowledge on solving the problem in implementation of ICT in ELT. In short, the result showed that most of student teachers were able to integrate ICT in the classroom, so it can be concluded that student teachers who have a good perceived knowledge can apply the use of ICT in a classroom. Regardless, the students’ teachers still need to empower themselves to be adaptable in using ICT tools in the future.Keywords: ICT; perceived knowledge; student teacher.